ІНФОРМАЦІЙНЕ ЗАБЕЗПЕЧЕННЯ ОЦІНКИ ЕКОНОМІЧНОГО ЗБИТКУ ВІД НИЗЬКОЇ ЯКОСТІ ЕЛЕКТРОЕНЕРГІЇ В СИСТЕМІ РОЗВИТКУ РЕГІОНАЛЬНОГО РИНКУ ЕЛЕКТРОЕНЕРГІЇ - Samoylenko, I.O. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2012)
The paper presents methodical recommendations developed to formalize the consideration of electricity quality as a basis for forming a relevant information support in the system of the regional electricity market development. It provides the improvement of the system of relations on the electricity market and protection of consumers’ rights.